The pharmacological properties and medicinal potential of Chromolaena odorata: a review / Nur Amirah Aziz ... [et al.] - Aziz, Nur Amirah; Mohamad, Mashani; Mohsin, Hannis Fadzillah; Mohamad Nor Hazalin, Nurul Aqmar; Abdul Hamid, Khuriah (Faculty of Pharmacy, 2020)
Chromolaena odorata Linn (L.) King and Robinson, which is locally known as 'Pokok Kapal Terbang' is one of the most gradual invasive weeds in Asia. The C. odorata species is distributed extensively in many areas and grow well in a wide range of habitats, especially moist and cold areas. The species, mainly the biotype found in Asia and West Africa, have been vastly used as a medicinal herb and are well-accepted among Asians over the past few decades for its medicinal properties. The literature revealed remarkable ethnopharmacological properties of this plant such as antibacterial, anti-inflammatory, antioxidant and analgesic activity. Other medicinal uses include its potential in wound healing treatment, skin infection as well as to treat stomach problems. The presence of various active chemical constituents such as phenolic, essential oils and flavonoid compounds in the leaves and root extracts of C. odorata is reported to have essentially contributed to its medicinal properties. Therefore, this review aims to give an overview of the phytochemical constituents, the bioactivities and potential medicinal properties of C. odorata.